Analisa Kawasan Keselamatan Operasi Keselamatan Penerbangan Dalam Rangka Pengoperasian Dan Pengembangan Bandar Udara Fatmawati Soekarno Bengkulu - Nunuk Pratiningsih; M. Budi Kuntjoro; Togi Adnan Maruli Sinaga (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
Obstacle Limitation Surface was the requirement for air transport safety. Indonesia as Contracting State of United Nation Organization had been formulated this rule by Basic Law on Civil Aviation. The aimed of this research is to analys the implementation of KKOP related to the airport operation and airport development refer to Fatmawati Soekarno Master Plan No. 576 Tahun 2015 tentang Rencana Induk Bandar Udara Fatmawati Soekarno. UU No. 1 Tahun 2009 tentang penerbangan was clearly mentioned that Local Goverment becoming responsible to control and conduct the air space near the airport operation as ilustrated in the Obstacle Limitation Surface in order to make secure the aviation safety and aircraft operation. UU No. 23 Tahun 2014 tentang Pemerintah Daerah had been not mentioned yet to accept in the operational activity to control and conduct in this air space that had been entrusted in the part section of UU. No. 1 Tahun 2009 tentang Penerbangan. Furthermore, this research as inputing program to civil aviation regulator and local goverment to make optimum coordination.